Markups and export pricing - Joakim Gullstrand; Karin Olofsdotter; Susanna Thede (Lund University, School of Economics and Management, Department of Economics, 2011)
We analyze empirically product-price variation across export destinations using detailed firm-product data. Most recent studies using highly disaggregated data emphasize variations in product quality as an explanation as to why firms charge different prices for the same product on different export markets. In this paper, we take an alternative approach and assume that variations in firms' export prices reflect market segmentation and investigate the relationship between price variation and average firm markup. We study an entire supply chain in order to see how price discrimination varies across sectors with different distribution networks. Specifically, we make use of firm-level data for exporting firms in the Swedish food supply chain. The results offer new information about the behavior of exporting firms. Hence, for the food-processing industry, firms with greater ability to discriminate between markets are associated with a higher markup. However, the results also reveal that markups are a complex function of firm characteristics and that the price-setting behavior of firms in the manufacturing sector is not necessarily observed in other sectors of the supply chain.
Keywords: D40; F12; F14; 330; Markups; Export prices; Price discrimination; Firm-level data